Pengaruh Budaya Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan KPP Pratama Jakarta Tebet - Choya Pari; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of Organizational Culture and Work Objectives on Employee Performance at KPP Pratama Jakarta Tebet. There are three variables in this study which include organizational culture, job satisfaction and employee performance. This study uses quantitative methods through google form by distributing questionnaires. The results of distributing questionnaires were used as measuring tools in data collection techniques because researchers could not come directly to the research site. The data collection technique is done online. From the results of the questionnaire distribution, the number of employees who filled out the questionnaire was 60 respondents who were employees of KPP Pratama Jakarta Tebet. The sampling technique in this study, the use of quota sampling technique which is from non-probability sampling and data analysis processed using the SPSS 22 application. The results of the study shows that the organizational culture variable has no significant effect on employee performance, the job satisfaction variable has a significant influence on employee performance and the organizational culture variable and job satisfaction simultaneously have a significant influence on employee performance.